1992
DOI: 10.1037/0022-0167.39.3.306
|View full text |Cite
|
Sign up to set email alerts
|

Memory for therapeutic events, session effectiveness, and working alliance in short-term counseling.

Abstract: Relationships among participants' assessments of the working alliance, effectiveness of counseling sessions, and memories for important therapeutic events were investigated in 10 counseling dyads. Results indicated that counselors exhibited greater specificity of recall of important events for sessions rated as more effective and showed greater specificity of recall than did clients. Counselors evidenced a statistically reliable increase in the bond aspect (quality of counselorclient relationship) of the worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
2
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 24 publications
2
61
2
1
Order By: Relevance
“…Perhaps a measure of learning from clients that parallels a measure of important events in therapy (e.g., Cummings, Martin, Hallberg & Slemon, 1992) could be developed. The measure could be an easy, open-ended, paper-and-pencil means of identifying the most important lessons therapists are taking away from a therapy session and/or relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps a measure of learning from clients that parallels a measure of important events in therapy (e.g., Cummings, Martin, Hallberg & Slemon, 1992) could be developed. The measure could be an easy, open-ended, paper-and-pencil means of identifying the most important lessons therapists are taking away from a therapy session and/or relationship.…”
Section: Discussionmentioning
confidence: 99%
“…However, these different dimensions of the alliance may have different emphasis throughout the therapeutic process according to therapy participants (Cummings, Martin, Hallberg, & Slemon, 1992;Fitzpatrick, Iwakabe, & Stalikas, 2005;Horvath & Marx, 1991). Webb et al (2011), found that the agreement on tasks and goals factor is a better predictor of symptomatic changes in CBT than the relationship factor (bond).…”
Section: The Alliance As a Multi-dimensional Phenomenonmentioning
confidence: 98%
“…Because important events tend to capture the essence of a therapy experience for clients, they should provide helpful information to explain why change might be occurring for clients. Other researchers (Cummings, Hallberg, Martin, & Slemon, 1992;Cummings, Martin, Hallberg, & Slemon, 1992;Cummings, Slemon, & Hallberg, 1993;Heppner, Rosenberg, & Hedgespeth, 1992;Mahrer & Nadler, 1986;Martin, Paivio, & Labadie, 1990;Martin & Stelmaczonek, 1988) have used important events in individual therapy to study change processes by categorizing events into five categories describing therapeutic processes. The only group therapy study which included important events was Kivlighan and Goldfine (1991), who asked university students to indicate critical incidents for each personal-growth session.…”
Section: Lmportant Events In Group Therapymentioning
confidence: 99%
“…The Important Events Questionnaire (Cummings, Martin, Hallberg, & Slemon, 1992). Shown in Appendix I, this questionnaire contains five questions, three of which were used in the present study: ( Outlines and sample exercises from the manuai are shown in Appendix J.…”
mentioning
confidence: 99%